1993
DOI: 10.1152/ajpcell.1993.264.3.c559
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate potentiation of excitation-contraction coupling in mammalian skeletal muscles

Abstract: The action of perchlorate (ClO4-), an agonist of the voltage sensor in excitation-contraction (EC) coupling, has been examined using bundles of intact muscle cells, isolated membrane vesicles [sarcoplasmic reticulum (SR) and transverse tubule (TT)], and cultured myotubes. The effect of ClO4- on mechanical parameters was investigated in isolated murine limb muscles. The presence of ClO4- (5 or 10 mM) greatly increased twitch tension ( > 250%), slightly enhanced tetanic tension, and increased K contracture tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…However, perchlorate also increases the rate of calcium release from isolated SR vesicles (Gallant et al, 1993;Fruen et al, 1994) indicating action on the SR as well. Recently it was suggested that perchlorate acts to enhance charge movement by feedback from SR to the TT possibly via elevated myoplasmic calcium (Pizarro et al, 1991;Gonzales and Rios, 1993).…”
Section: Effects Of Caffeine and Perchloratementioning
confidence: 97%
See 3 more Smart Citations
“…However, perchlorate also increases the rate of calcium release from isolated SR vesicles (Gallant et al, 1993;Fruen et al, 1994) indicating action on the SR as well. Recently it was suggested that perchlorate acts to enhance charge movement by feedback from SR to the TT possibly via elevated myoplasmic calcium (Pizarro et al, 1991;Gonzales and Rios, 1993).…”
Section: Effects Of Caffeine and Perchloratementioning
confidence: 97%
“…Both agents had no significant effect on caffeine contractures at higher [K'lo. Perchlorate enhancement of K-conditioned caffeine contractures Perchlorate (0.1-5 mM) significantly potentiates twitch force of mouse edl (Gallant et al, 1993) and soleus muscles (Dulhunty et al, 1992) in a dose-dependent manner but has little effect on tetanus tension and does not alter twitch time course (Gallant et al, 1993). At 10 mM or greater perchlorate, mouse edl twitch kinetics are markedly altered (Gallant et al, 1993).…”
Section: 5)mentioning
confidence: 99%
See 2 more Smart Citations
“…Charge movement arises from the transverse (T) tubule dihydropyridine receptor, indicating that perchlorate may act at the T-tubule. Perchlorate also potentiates E-C coupling and increases contracture force, electrically evoked twitches [11,12] and K -contractures [11]. More recently, perchlorate has been shown to activate purified RyR channels in lipid bilayers [21] and to increase Ca 2+ release from native SR vesicles [4,11], leading to the suggestion that the RyR may be the primary site of perchlorate's action in skeletal muscle [21,29].…”
Section: Introductionmentioning
confidence: 99%